PENERAPAN PROSEDUR OPERASIONAL STANDAR MAKEUP ROOM OLEH ROOMBOY AYANA RESORT AND SPA, BALI - Pratiwi, Suci (RC-INSTITUT, 2019)
This research aimed to find out the implementation of standard procedure conducted by room boys of AYANA Resort and Spa, BALI. This research usedseven(7) indicators of implementation procedures: knocking the room door, opening the curtains of the window, striping, making bed, cleaning the bath room, dusting and rechecking. This research is descriptive research with qualitative data. The population in this research was eight (8) room boys of Ayana Resort and Spa. The data were collected through interview, observation, and documentation. They were then analyzed by reducing, presenting, drawing conclusion, and verification of the data. The result of this research showed that the standard procedures of make-up room have been conducted completely and properly by 8 room boys of Ayana Resort and Spa, BALI. All indicators but cleaning the bath room have been implemented by room boys. Only 75% of room boys implemented cleaning the bath room indicator properly.